1996
DOI: 10.1046/j.1365-2265.1996.642464.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cortisol, PRL, ACTH, AVP and corticotrophin releasing hormone responses to direct current cardioversion and electroconvulsive therapy

Abstract: Significant hypothalamic-pituitary-adrenal activation and PRL release occur in response to both cardioversion and ECT. AVP may have an important role in mediating the acute ACTH response to electrical stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 0 publications
0
26
0
1
Order By: Relevance
“…Our data do not support the hypothesis that neuroactive steroids determine the long-term beneficial effects of ECT in depressive disorders, although an effect of ECT on brain concentrations of neuroactive steroids cannot be excluded. Thus, other effects including a potential impact of ECT on the hypothalamic pituitary adrenal (HPA) system, such as an acute stimulatory effect (Florkowski et al, 1996) and a long-term reduction of HPA axis overdrive (Grunhaus et al, 1987), or effects on neurotrophic factors (Altar, 1999;Smith et al, 1997), are more likely contributing factors for the clinical efficacy of ECT.…”
Section: Discussionmentioning
confidence: 99%
“…Our data do not support the hypothesis that neuroactive steroids determine the long-term beneficial effects of ECT in depressive disorders, although an effect of ECT on brain concentrations of neuroactive steroids cannot be excluded. Thus, other effects including a potential impact of ECT on the hypothalamic pituitary adrenal (HPA) system, such as an acute stimulatory effect (Florkowski et al, 1996) and a long-term reduction of HPA axis overdrive (Grunhaus et al, 1987), or effects on neurotrophic factors (Altar, 1999;Smith et al, 1997), are more likely contributing factors for the clinical efficacy of ECT.…”
Section: Discussionmentioning
confidence: 99%
“…No change in corticoreleasing factor in blood was found after ECT (Widerlöw et al, 1989;Florkowski et al, 1996) but plasma levels of corticotropin increased (Widerlöw et al, 1989).…”
Section: Hormones and Neuropeptidesmentioning
confidence: 87%
“…Cell growth Scott et al (2000), Madsen et al (2002); increase Synaptic connectivity Gombos et al (1999); increase Stewart and Reid (1993); Reid and Stewart (1997); increase Florkowski et al (1996); increase GH Abrams (1992); inconsistent Prolactin Florkowski et al (1996), Fink and Nemeroff (1989), Fink (1989), Abrams and Swartz (1985) Sackeim et al (1986), Abrams and Swartz (1985) TSH Aperia et al (1985), Fink and Nemeroff (1989) Bergsholm (1999), Ishihara et al (1999); 5-HT-, NA-, cholinergic-, glutaminergic-and GABAergic systems, adenosin. A1-receptor 5-HT2A, decrease in sensitivity, (Plein and bark, 2000) Activation of 5-HT and DA transmission, Yoshida et al (1998), Juckel et al (1999); stim.…”
Section: Neurotrophic Factorsfcell Growth and Neuroplasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…For acute metabolic effects of ECT, it was reported that cholesterol and glucose levels are increased 20 min after ECT. 2 ECT may increase glucose levels via cortisol, 3 norepinephrine 4 or insulin. 5 The mechanisms linking ECT and changes in blood lipids are unknown.…”
mentioning
confidence: 99%